2018
DOI: 10.1108/jkm-12-2017-0558
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge risk management in the public sector: insights into a Swedish municipality

Abstract: Purpose This study aims to contribute to the understanding of knowledge risk management (KRM) and a range of related knowledge management practices in the public sector through a case study conducted in a Swedish municipality. Design/methodology/approach A single case study was conducted in a Swedish municipality involving two offices. Data were collected through an online survey, group interviews and group exercises involving members of the offices who represented different functions, roles and age groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
0
22
0
3
Order By: Relevance
“…From a practical point of view, the findings may provide forward-looking organizations some useful ideas for developing and executing knowledge strategies that facilitate a better Theme Author(s) and subject of interest Awareness raising Pender (2001) draws attention to having a broader approach to probability risk management, one that incorporates incomplete knowledge as well Neef (2005) highlights the contribution of KRM to the global economy Nielsen (2006) points at general requirements of risk management tools Marabelli and Newell (2012), by using a practice perspective of knowledge, hope to initiate a rethinking process with regard to knowledge sharing processes (and associated risks) to shed light on issues associated with strategically managing collaborative networks Mariano and Casey (2015) discuss negative impacts of innovation with a particular focus on the relationship between knowledge complementarities, organizational learning and absorption processes Conditions for improved KM/KRM Perrott (2007) proposes a tentative process model for managing knowledge van der Spek et al (2009) propose a four-step methodology to strengthen weak lateral relations through knowledge management Frameworks for improved K(R)M Kumar (2002) suggests the theory of real options as a useful framework for understanding risk hedging in IT projects Harland et al (2003) present and discuss experiences of using a tool intended to identify, assess and manage supply network risk Rodriguez and Edwards (2008) show the contribution of KMS to support ERM processes Tserng et al (2009) propose an activity and knowledge-flow analysis of the RM workflow. The framework also comprises the calculation of a risk value of each risk subclass and class Massingham (2010) offers a solution, based on the use of KM tools and techniques, to enable individuals to generate a deeper insight into the real nature of organizational risk Alhawari et al (2012) propose a comprehensive framework and methodology for using knowledgebased risk management processes within IT organizations Durst et al (2018) propose a KRM framework to have a base for future investigations into issues associated with KRM and KRM-related practices Knowledge loss Treleaven and Sykes (2005) found that demonstrably, tacit and heuristic knowledge have been major losses, disrupted and increasingly replaced by corporate managerialism instituting more abstract knowledge to generalize policies and procedures Ward and Wooler (2010) suggest a number of actions managers could take to avoid knowledge loss in times of economic downturns Jafari et al (2011) developed a six-step integrated model that manages the loss of critical knowledge because of retirement, internal replacement or quitting personnel Schmitt et al (2011)...…”
Section: Discussionmentioning
confidence: 99%
“…From a practical point of view, the findings may provide forward-looking organizations some useful ideas for developing and executing knowledge strategies that facilitate a better Theme Author(s) and subject of interest Awareness raising Pender (2001) draws attention to having a broader approach to probability risk management, one that incorporates incomplete knowledge as well Neef (2005) highlights the contribution of KRM to the global economy Nielsen (2006) points at general requirements of risk management tools Marabelli and Newell (2012), by using a practice perspective of knowledge, hope to initiate a rethinking process with regard to knowledge sharing processes (and associated risks) to shed light on issues associated with strategically managing collaborative networks Mariano and Casey (2015) discuss negative impacts of innovation with a particular focus on the relationship between knowledge complementarities, organizational learning and absorption processes Conditions for improved KM/KRM Perrott (2007) proposes a tentative process model for managing knowledge van der Spek et al (2009) propose a four-step methodology to strengthen weak lateral relations through knowledge management Frameworks for improved K(R)M Kumar (2002) suggests the theory of real options as a useful framework for understanding risk hedging in IT projects Harland et al (2003) present and discuss experiences of using a tool intended to identify, assess and manage supply network risk Rodriguez and Edwards (2008) show the contribution of KMS to support ERM processes Tserng et al (2009) propose an activity and knowledge-flow analysis of the RM workflow. The framework also comprises the calculation of a risk value of each risk subclass and class Massingham (2010) offers a solution, based on the use of KM tools and techniques, to enable individuals to generate a deeper insight into the real nature of organizational risk Alhawari et al (2012) propose a comprehensive framework and methodology for using knowledgebased risk management processes within IT organizations Durst et al (2018) propose a KRM framework to have a base for future investigations into issues associated with KRM and KRM-related practices Knowledge loss Treleaven and Sykes (2005) found that demonstrably, tacit and heuristic knowledge have been major losses, disrupted and increasingly replaced by corporate managerialism instituting more abstract knowledge to generalize policies and procedures Ward and Wooler (2010) suggest a number of actions managers could take to avoid knowledge loss in times of economic downturns Jafari et al (2011) developed a six-step integrated model that manages the loss of critical knowledge because of retirement, internal replacement or quitting personnel Schmitt et al (2011)...…”
Section: Discussionmentioning
confidence: 99%
“…Se destaca que la Entidad avanzó en el diseño del modelo y en la aplicación de herramientas de GC, pero es importante que se consideré la implementación de indicadores de gestión que permitan analizar el impacto de la misma, en términos de la eficiencia y la efectividad (Ahn et al, 2009). Los altos directivos son responsables de la implementación de los sistemas de gestión (Jain y Jeppesen, 2013), por lo cual su compromiso y respaldo con las prácticas de GC y la comprensión de su valor son fundamentales para facilitar la asignación de recursos que permitan desarrollar y compartir el conocimiento en la organización (Von Krogh, 1998; Chong et al, 2011); de manera que también permitan a los empleados destinar tiempo para participar de las actividades de GC, aspecto que también debe ser considerado en la Entidad (Durst et al,2018) . Por lo anterior, y teniendo en cuenta que los resultados del estudio evidencian que es necesario fortalecer la participación de los líderes, se deben desarrollar estrategias para la consolidación de una cultura organizacional que priorice el conocimiento, dado que la actitud de apoyo de éstos influye en las prácticas de GC de manera favorable (Davenport et al, 1998).…”
Section: Momento 3 Análisis De Resultadosunclassified
“…They should also feel free and report immediately about possible risks they may detect in their daily work and then in a next step discuss with other organization members the likely risk potential and, if high, identify and initiate proper countermeasures. These activities will be easier when the company has implemented both a systematic approach to KRM and a knowledge risk-aware culture (Durst et al , 2018). Employees should also actively seek training modules/programs/actions that could be run inside or outside the small firm to make sure that it is always in the position of the latest knowledge; here with regard to the pros and cons of new technological innovations.…”
Section: Discussionmentioning
confidence: 99%